Effects of Zostera marina on the patterns of spatial distribution of sediments and macrozoobenthos in the boreal lagoon of Furen (Hokkaido, Japan). (October 2017) - Magni, P.; Como, S.; Kamijo, A.; Montani, S.
Abstract: Understanding patterns of spatial variations in benthic seagrass assemblages is a central issue in seagrass ecology. However, how patterns of spatial variations in macrozoobenthos and associated sediments differ between vegetated and unvegetated areas remain largely unexplored. In the present study, two different habitats represented by dense Zostera marina beds ( Zostera ) and unvegetated sediments ( Bare ) were compared at three locations, 100's meters apart, located at progressive distance from the Furen river in the boreal lagoon of Furen (Hokkaido, Japan). We tested the hypothesis that Z. marina influences the patterns of spatial distribution of abiotic and biotic components along an environmental (estuarine) gradient. The results showed considerable differences between Zostera and Bare, as well as between and within locations, in the distribution of both sediment variables (mud, total organic carbon [TOC] and total nitrogen, acid volatile sulfide, chlorophyll- a and pheopigments) and macrozoobenthic assemblage metrics (total number of species [ S ], Shannon-Weiner diversity index [ H′ ], total abundance and abundance of dominant species). TOC content, associated to a high mud content, was highest in Bare irrespective of differences between locations (all being above a critical TOC threshold of 3.6%), while S and H′ were higher in Zostera than in Bare at all locations. Significant location x habitat effects were found in the abundance of dominant species, represented mainly by mollusks and crustaceans. Furthermore, the proportions of spatial variance were greater at the scale of replicates (meters apart) than at the scale of stations (10's meters apart) for both sediment variables and the dominant species. Importantly, for the dominant species the spatial variance at the smaller scale was much higher in Zostera than in Bare, indicating that at the scale of meters Zostera beds increase the patchiness in the spatial distribution of individuals compared to bare sediments. Overall, our results demonstrate that Z. marina has a strong effect on the spatial heterogeneity in the intensity of the ecological processes influencing patterns of sediment and macrozoobenthos distribution along an environmental gradient. The present study provides a general framework to evaluate patterns of spatial distribution across various scales within several hundreds of meters in seagrass-dominated, eutrophic coastal lagoons. Graphical abstract: Highlights: Spatial distribution of sediments and macrozoobenthos in Zostera and Bare assessed. TOC content higher in Bare, species richness and diversity higher in Zostera. Significant location x habitat effects in the abundance of dominant species. Spatial variance at the smallest scale (meters apart) higher in Zostera than in Bare. Z. marina affects the patchiness in the intensity of ecological processes.